Mismatching Skills, The Currect Problem Among Vocational Graduates in East Java - Luthfi Indana; Blima Oktaviastuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Preliminary study at Trenggalek Regency show that most of vocational graduates from multimedia department work as shopkeeper on the department stores or as a salesman/saleswoman. This fact realize us that the purpose of vocational high school is not achieved yet. The research aims to describe and present mismatching skills data among vocational graduates. This study is descriptive with quantitative approach which focuses on multimedia department. The data will gained from 2 public schools. This data is collected from students who graduate on 2017 school year in SMK Raya and three generation graduates from SMKN Jaya. The method that been used are documentation and interview from career center at each school. As a result from 279 vocational graduates on multimedia department, graduates who study in the suitable field is 9%, who continue their study in the different field 27%, who work on the appropiate field approximately 18%, who get their work in the different field around 38%, and 8% of graduates still in the waiting period. Finally, the conclusion is vocational graduates can’t fill yet the job market at suitable field. Therefore, role of all education stakeholder are needed to reduce mismatching skills between background of study and field of work.